Utilización de la boleta de auxilio por parte de la víctima en los casos de violencia intrafamiliar, como prueba inducida para engañar al juzgador en el cantón Guaranda. - Rea Tocta, Fabián Donaldo (2022)
The present investigation carries out a legal analysis regarding the misuse of the aid ticket by the victim in cases of domestic violence as induced evidence to deceive the judge and the effects that it produces on the accused person within the criminal process in this type of violence, since it is used as an instrument of revenge, given that the Comprehensive Organic Criminal Code has not established a suitable procedure to grant the respective aid tickets, since in Ecuadorian legislation it is enough that the alleged victim of domestic violence go to the competent body and request the respective ticket, which is granted without previously having verified the facts that are denouncing, likewise, the present investigation also focuses on determining the purpose of the ticket for help in cases of violence intrafamilial and what are the consequences that develop due to non-compliance or protective measures. Within the present investigation, a quantitative approach was used, which is developed through an inductive process in order to determine the violations of the rights of the alleged offenders in crimes of violence against women and members of the family nucleus for the use inadequate protection measures, among the relevant results of the investigation is that the lack of a procedure that regulates the granting of the aid ticket directly violates the principle of presumption of innocence.